Em kiểm tra lại đề bài nhé, phương trình này không giải được.
Biểu thức thứ 2 là \(\left(2x^2-3x+2\right)\) thì hợp lý hơn.
\(\left(2x^2-3x+2+2x\right)\left(2x^2-3x+2\right)-8x^2=0\)
\(\Leftrightarrow\left(2x^2-3x+2\right)^2+2x\left(2x^2-3x+2\right)-8x^2=0\)
\(\Leftrightarrow\left(2x^2-3x+2\right)^2+4x\left(2x^2-3x+2\right)-2x\left(2x^2-3x+2\right)-8x^2=0\)
\(\Leftrightarrow\left(2x^2-3x+2\right)\left(2x^2-3x+2+4x\right)-2x\left(2x^2-3x+2+4x\right)=0\)
\(\Leftrightarrow\left(2x^2-3x+2\right)\left(2x^2+x+2\right)-2x\left(2x^2+x+2\right)=0\)
\(\Leftrightarrow\left(2x^2-3x+2-2x\right)\left(2x^2+x+2\right)=0\)
\(\Leftrightarrow\left(2x^2-5x+2\right)\left(2x^2+x+2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}2x^2-5x+2=0\\2x^2+x+2=0\left(vô-nghiệm\right)\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{1}{2}\end{matrix}\right.\)